Evaluación de la imagen de marca y su influencia en el posicionamiento de los restaurantes de la ciudad de Chone - Zambrano Bravo, Cristhian Jair (2023)
This study was developed with the objective of evaluating the brand image and its influence on the positioning of gourmet restaurants in the city of Chone. For the fulfillment of this objective, methodologies were developed such as the selection of indicators through Meta-analysis, these indicators were expressed in evaluation mechanisms such as the interview and the survey to which a reliability analysis was applied through Cronbach's alpha test, together with the Pearson correlational method was used with a significance level of 5% to demonstrate the relationship between the research variables, subsequently a cause and effect diagram was forged to determine the inconsistencies of the study, to which improvement strategies were proposed through the 5W+1H matrix. The results show inconsistencies in the variables of brand image and positioning, in indicators such as Corporate Image, Functional Image, Reputation, Notoriety, Brand Loyalty, Brand Association and Brand Image, as well as a weak and moderate significant linear correlation between the study variables, due to the little interrelation between the evaluated indicators, the detected inconsistencies were sketched in a cause and effect diagram to which strategies focused on the general resolution of the indicator were generated. Gourmet restaurants should emphasize the resolution of the problems detected, since, if they are maintained, it would influence the image that users have of these establishments and would affect their positioning in the market.